Adventures in social research data analysis using IBM SPSS statistics - Babbie, Earl R.; Zaino, Jeanne; Wagner, William E. (William Edward) (Los Angeles London SAGE, 2023)
This text provides a practical, hands-on introduction to data conceptualization, measurement, and association through active learning. Students get step-by-step instruction on data analysis using the latest version of SPSS and the most current General Social Survey data. The text starts with an introduction to computerized data analysis and the social research process, then walks users through univariate, bivariate, and multivariate analysis using SPSS. The book contains applications from across the social sciences-sociology, political science, social work, criminal justice, health-so it can be used in courses offered in any of these departments. The Eleventh Edition uses the latest general Social Survey (GSS) data, and the latest available version of SPSS. The GSS datasets now offer additional variables for more possibilities in the demonstrations and exercises within each chapter"--
Includes bibliographical references and index.
Keywords: SPSS for Windows; Social sciences -- Statistical methods -- Computer programs